Cloning and expression of pigC gene in Escherichia coli - Trung, Do Minh; Quynh, Do Hai; Tien, Tran Viet; Bac, Nguyen Duy; Tuyen, Do Thi; Duong, Nguyen Thuy (Vietnam Journal of Biotechnology, 2020)
Prodigiosin (Pg), which is particularly of interest because of anticancer and antimicrobial activities, can be produced through the PigC-catalyzed condensation reaction of 4-methoxy-2, 2’-bipyrrole-5-carboxyaldehyde (MBC) and 2-methyl-3-amylpyrrole (MAP). Therefore, the PigC protein plays an important role in prodigiosin biosynthetic pathway. However, studies related to PigC protein have not been carried out in Vietnam yet. In this work, the pigC gene was cloned and expressed in Escherichia coli DH10B and BL21 (DE3), respectively. Using PCR and universal primers, we amplified a fragment of 3 kb covering entire coding region of the pigC gene from Serratia sp. strain M5. The pigC gene was inserted into pJET1.2 vector, and then transformed into E. coli DH10B. The sequence of a recombinant vector pJET1.2/pigC was evaluated by using whole colony PCR amplification. Sequence alignment results revealed that the obtained pigC gene possesses 71.5% and 75.4% of nucleotide identity in comparison with two strains, Serratia 39006 and Serratia sp. AS9 published in GenBank with their respective accession numbers of AJ833001 and CP002773. The recombinant vector pJET1.2/pigC was used to reamplify pigC, and the acquired amplicon was inserted into pET22b vector at the site of HindIII and XhoI. The clone E. coli BL21 (DE3) containing recombinant vector pET22b/pigC was expressed in the auto-induced medium. The presence of PigC protein in the lysate was identified as a 100 kDa band through Western Blot analysis using anti his-tag antibody. Afterward, the PigC protein was purified by Ni-NTA column, and its expression level was quantified through SDS-PAGE analysis. The results of our study provide a potential material for producing prodigiosin from recombinant protein in Vietnam